Cyprus : Eighth Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Cyprus. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses Cyprus' Eighth Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria (PC). Cyprus continues to recover from the crisis, and program performance remains generally strong. Risks to the program remain, although their impact would likely be manageable. The domestic political situation remains a challenge to policy implementation. Despite the reduced real and financial linkages between Greece and Cyprus, developments in Greece have the potential to affect Cyprus through the confidence channel. Based on the continued progress under the program and policy commitments going forward, the IMF staff supports the completion of the eighth review and the proposed modifications of PCs.